Case studies from the perspectives of aged care residents on turning and positioning: Implications for technical progress in pressure injury prevention. Issue 3 (2022) - Kapp, Suzanne; Gerdtz, Marie; Gefen, Amit; Kendall, Fiona; Tull, Jennifer; Oliver, Natalie; Santamaria, Nick
No abstract available